An international multicenter retrospective analysis of patients with extranodal marginal zone lymphoma and histologically confirmed central nervous system and dural involvement. (5th December 2019) - Sunderland, Andrew J.; Steiner, Raphael E.; Al Zahrani, Musa; Pinnix, Chelsea C.; Dabaja, Bouthaina Shbib; Gunther, Jillian R.; Nastoupil, Loretta J.; Jerkeman, Mats; Joske, David; Cull, Gavin; El‐Galaly, Tarec; Villa, Diego; et al.
Abstract: Marginal zone lymphoma of the central nervous system (CNS MZL) is rare. The clinical features, treatment, and prognosis are not well characterized. We performed a multicenter retrospective study of CNS MZL. Twenty‐six patients were identified: half with primary and half with secondary CNS involvement. The median age was 59 years (range 26‐78), 62% female and 79% with ECOG performance status ≤ 1. The most common disease site was the dura (50%). Treatment was determined by the treating physician and varied substantially. After a median follow up of 1.9 years, the estimated 2‐year progression‐free (PFS) and overall survival (OS) rates were 59% and 80%, respectively. Secondary CNS MZL was associated with 2‐year OS of 58%. CNS MZL is rare, but relative to other forms of CNS lymphoma, outcomes appear favorable, particularly among the subset of patients with dural presentation and primary CNS presentation. Abstract : Marginal zone lymphoma of the central nervous system (CNS MZL) is rare. In this multicenter retrospective study of 26 patients, the estimated 2‐year overall survival rate was 80%. Outcomes appear favorable, particularly among the subset of patients with primary dural presentation.